Pyrroloquinoline Quinone Alleviates Jejunal Mucosal Barrier Function Damage and Regulates Colonic Microbiota in Piglets Challenged With Enterotoxigenic Escherichia coli - Huang, Caiyun; Ming, Dongxu; Wang, Wenhui; Wang, Zijie; Hu, Yongfei; Ma, Xi; Wang, Fenglai (Frontiers in Microbiology, 2020)
This study aimed to evaluate the effect of dietary supplementation with pyrroloquinoline quinone (PQQ) on gut inflammation and microbiota dysbiosis induced by enterotoxic Escherichia coli. Twenty Duroc × Landrace × Yorkshire crossbred barrows were assigned to four groups: two Escherichia coli K88 challenge groups and two non-challenge groups, each provided a basal diet supplemented with 0 or 3 mg/kg PQQ. On d 14, piglets were challenged with 10 mL 1 × 109 CFU/mL of Escherichia coli K88 or PBS for 48 h. The villus height and villus height/crypt depth ratio of the Escherichia coli K88-challenged group supplemented with PQQ was significantly reduced than in the non-supplemented challenge group (P < 0.05), while levels of jejunal zonula occludens-3, diamine oxidase, secretory immunoglobulin A, interleukin-10, and interleukin-22 proteins were higher (P < 0.05), as were the activities of glutathione peroxidase, total superoxide dismutase and total antioxidant capability (P < 0.05). Moreover, PQQ supplementation alleviated an increase in levels of mucosal inflammatory cytokines and reduced the activity of NF-κB pathway by Escherichia coli K88 (P < 0.05). Gene sequencing of 16S rRNA showed dietary supplementation with PQQ in Escherichia coli K88-challenged piglets attenuated a decrease in Lactobacillus count and butyrate, isobutyrate level, and an increase in Ruminococcus and Intestinibacter counts, all of which were observed in non-supplemented, challenge-group piglets. These results suggest that dietary supplementation with PQQ can effectively alleviate jejunal mucosal inflammatory injury by inhibiting NF-κB pathways and regulating the imbalance of colonic microbiota in piglets challenged with Escherichia coli K88.